2022
DOI: 10.1101/2022.09.22.509106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal pentraxin Nptx2 regulates complement activity in the brain

Abstract: Complement overactivation mediates microglial synapse elimination in neurological diseases like Alzheimer disease and frontotemporal dementia (FTD), but how complement activity is regulated in the brain remains largely unknown. We identified that the secreted neuronal pentraxin Nptx2 binds complement C1q and thereby regulates its activity in the brain. Nptx2-deficient mice show increased complement activity and C1q-dependent microglial synapse engulfment and loss of excitatory synapses. In a neuroinflammation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…NPTX2 is a neuronal pentraxin, implicated in synaptic plasticity and excitatory synaptogenesis [6,7]. It has recently been shown that NPTX2 interacts with the complement protein C1q to restrict microglia complement-dependent synapse engulfment in neurodegeneration [8]. Despite the pentraxin superfamily being known for its evolutionarily conserved roles in innate immunity [9], the function of Nptx2 in the context of inflammation has not been studied.…”
mentioning
confidence: 99%
“…NPTX2 is a neuronal pentraxin, implicated in synaptic plasticity and excitatory synaptogenesis [6,7]. It has recently been shown that NPTX2 interacts with the complement protein C1q to restrict microglia complement-dependent synapse engulfment in neurodegeneration [8]. Despite the pentraxin superfamily being known for its evolutionarily conserved roles in innate immunity [9], the function of Nptx2 in the context of inflammation has not been studied.…”
mentioning
confidence: 99%